2017
DOI: 10.1016/j.neuropsychologia.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Frontal alpha asymmetry predicts inhibitory processing in youth with attention deficit/hyperactivity disorder

Abstract: Introduction Atypical asymmetry in brain activity has been implicated in the behavioral and attentional dysregulation observed in ADHD. Specifically, asymmetry in neural activity in the right versus left frontal regions has been linked to ADHD, as well as to symptoms often associated with ADHD such as heightened approach behaviors, impulsivity and difficulties with inhibition. Clarifying the role of frontal asymmetry in ADHD-like traits, such as disinhibition, may provide information on the neurophysiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 51 publications
2
34
0
Order By: Relevance
“…Moreover, these results were specific to frontal regions only (F4-F3). Although in the present study the exact anatomical source for FAA remains unclear, previous studies conducted in the waking state have shown that FAA originates from the dorsolateral PFC (Ellis et al, 2017) and from the lateral and medial frontal gyri (Gable et al, 2015;Neal and Gable, 2016). This suggests that dream anger is most likely related to reduced activity in the right lateral PFC (lPFC).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Moreover, these results were specific to frontal regions only (F4-F3). Although in the present study the exact anatomical source for FAA remains unclear, previous studies conducted in the waking state have shown that FAA originates from the dorsolateral PFC (Ellis et al, 2017) and from the lateral and medial frontal gyri (Gable et al, 2015;Neal and Gable, 2016). This suggests that dream anger is most likely related to reduced activity in the right lateral PFC (lPFC).…”
Section: Discussionmentioning
confidence: 55%
“…It is important to note that the right PFC is involved not only in the regulation of negative affect, but also in inhibitory control in general (Bari and Robbins, 2013;Aron et al, 2014;Depue et al, 2016). Numerous studies conducted in the waking state have demonstrated an association between greater FAA (i.e., relatively less right frontal activity) and states and traits related to disinhibition, such as aggression (Harmon-Jones and Allen, 1998; Harmon-Jones and Sigelman, 2001), impulsivity (Gable et al, 2015;Neal and Gable, 2017), sensation seeking (Santesso et al, 2008), (positive and negative) urgency (Neal and Gable, 2016), response inhibition (Ellis et al, 2017), and risk-taking behavior (Gianotti et al, 2009). Moreover, studies using transcranial direct current stimulation and repetitive transcranial magnetic stimulation have shown that inhibition of the right, or stimulation of the left, lPFC leads to disinhibition (for review, see Kelley et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these results were specific to frontal regions only (F4-F3). Although, in the present study the exact anatomical source for FAA remains unclear, previous studies conducted in the waking state have shown that FAA originates from the dorsolateral PFC (59) and from the lateral and medial frontal gyri (48,60). This suggests that dream anger is most likely related to reduced activity in the right lateral PFC (lPFC).…”
Section: Discussionmentioning
confidence: 56%
“…It is important to note that the right PFC is involved not only in the regulation of negative affect, but in inhibitory control in general (63,64). Numerous studies conducted in the waking state have demonstrated an association between greater FAA (i.e., relatively less right frontal activity) and states and traits related to disinhibition, such as aggression (57,65), impulsivity (48,66), sensation seeking (67), (positive and negative) urgency (60), response inhibition (59), and risk-taking behavior (68). Moreover, studies using transcranial direct current stimulation (tDCS) and repetitive transcranial magnetic stimulation (rTMS) have shown that inhibition of the right, or stimulation of the left, lateral PFC leads to disinhibition (37).…”
Section: Discussionmentioning
confidence: 99%
“…The approach/withdrawal motivation model of EEG asymmetry suggests that greater relative left frontal activity is associated with approach-related tendencies, and greater relative right activity is associated with withdrawal-related tendencies [28]. A majority of the studies to date have examined the link between FAA and various psychopathological conditions, including depression [21,29,30,31] and ADHD [32,33]. Overall, these studies lend support to the motivational theory that both a behavioral inhibition system (BIS) and a behavioral activation system (BAS) drive our emotions and behaviors.…”
Section: Introductionmentioning
confidence: 99%